(untitled) (ENTHYMEMA, 2023)
The transformation processes that have affected the comics field between the 20th and 21st centuries are strictly linked with the digitization and integration of the media system. Alongside the affirmation of the graphic novel, which allows the comics to converge towards organic narrative arcs assumed from the literary novel, tendencies to boost the short genres of classic comics are outlined: the humorous strip, the fulminating cartoon, the self-contained comic board. The dizzying increase in the flows developed by the web favours the transposition, recirculation, stratification of such comics splinters, between analogue communication and digital communication. These are proposals that arise from the grassroots, from protagonists of social media creative participation or from renovators of underground culture. The interweaving of institutional aesthetic interaction and self-managed mediacy, while bound to the oligopoly of the platforms, opens up original opportunities for differentiation and enrichment of the comics experience.